Reproductive performances of local pigs in West African countries: A review - Dotché, Ogoudanan Ignace; Antoine-Moussiaux, Nicolas; Dehoux, Jean-Paul; FAROUGOU, SOUAÏBOU; Thilmant, Pierre; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2020)
The local pig is reared in all West Africa countries, and especially in small farms, playing so an important role in its preservation. This article reviews work done on reproductive performances of local pigs in West Africa. These performances focus on age at puberty, estrus and sex cycle, gestation length, prolificity, viability and growth before piglets weaning. Factors that can influence these parameters are included. Finally, the contribution of animal biotechnology to these performances improvement is discussed.
Keywords: Local pig; Performances; Reproduction; Biotechnology; West Africa